A case of extramammary inguinal Paget disease in a male patient: surgical treatment with an abdominal advancement cutaneous flap - Sisti, Andrea; Tassinari, Juri; Cuomo, Roberto; Milonia, Luca; Nisi, Giuseppe; Brandi, Cesare; D'Aniello, Carlo; Grimaldi, Luca (Acta Biomedica Atenei Parmensis, 2017)
Extramammary Paget disease (EMPD) is a rare neoplasm. The clinical case of a 55-year-old man with a two-year history of a pruritic, painless erythematous skin rash on the inguinal region and scrotum is described. After a delay due to improper diagnosis and improper treatments, the patient came to the attention of the Division of plastic surgery. He underwent a punch biopsy and the pathology report came back as EMPD. Surgical excision was carried out, and an abdominal advancement cutaneous flap was performed for the defect repair. This is the first description of a reconstruction after surgical removal of inguinal EMPD with a flap of this type and we think that this type of treatment can be useful and reliable for disease localization in the groin area, especially for patients that present an excess of abdominal skin.